Peningkatan Hasil Belajar Peserta Didik Melalui Metode Praktikum Kimia Sederhana di Kelas XII SMA YPPK Teruna Bakti Kota Jayapura - Fitria Rospitasari; Lusia Narsia Amsad; Ermiany Mangintek (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the improvement of students’ learning outcomes through the use of chemistry practicum methods in Grade XII of YPPK Teruna Bakti Jayapura Senior High School. The research was conducted in two cycles. Cycle I implemented a problem-based learning model with instructional material on preparing buffer solutions, while Cycle II used a discovery learning model with instructional material on acid–base titration. Data were collected through observation, interviews, documentation, and learning outcome tests. The total number of respondents in this study was 32 students. The results showed an increase in students’ learning outcomes through the use of chemistry practicum methods in both Cycle I and Cycle II, with average scores of 80 and 88.44, respectively, and average mastery percentages of 81.25% in Cycle I and 90.63% in Cycle II. The improvement in mastery learning reached 9.38%, with the mastery percentage exceeding 75%. Students’ learning activities also increased from 73.44% in Cycle I to 76.39% in Cycle II, showing a 2.95% improvement. The findings from both cycles indicate an increase in students’ learning activities and learning outcomes through the implementation of chemistry practicum methods. The success of applying the chemistry practicum method in this study was influenced by the teacher’s skills, the availability of laboratory tools and materials, increased student learning motivation, and favorable laboratory conditions.